Policy Implementation: E-village Budgeting in Banyuwangi Regency - Entang Adhy Muhtar; Dody Hermana; Dewi Gartika; Riki Satia Muharam (Iapa Proceedings Conference, 2019)
e-Village Budgeting is an application about planning, administration and accountability of village financial management for all villages in Banyuwangi Regency which are website based and online with real time data. The purpose of making this Electronic Village Budgetting System (E-VB) application is to create transparency and accountability in village financial management. In general, the implementation of the Electronic Village Budgetting (E-VB) Policy has been running but has not been perfect. The implementor is still shackled with the old system, even though the system is new. This study aims to examine and analyze the implementation of Electronic Village Budgetting (E-VB) Policy in Banyuwangi Regency. The theory used in this study is the theory of policy implementation from Van Meter and Van Horn. The method used is a qualitative research method. The results showed that, from the aspect of resources, especially software and brainware, were still limited, from the disposition aspect there were different perceptions in the implementation of Electronic Village Budgetting. Research recommendations need "Interpretation", which is the same in terms of budgetary linkages and Information Technology (IT) in the Implementation of Electronic Village Budgetting Policy.